The Paraonidae (Annelida: Sedentaria) from Norway and adjacent seas, with two new species, four new records, and a redescription of Paraonides nordica Strelzov, 1968 based on type material - López, Eduardo; Sikorski, Andrey (Zootaxa, 2017)
Twenty-three species were identified from the study of 302 specimens belonging to the family Paraonidae which were collected from Norwegian and adjacent waters. In this work Cirrophorus brevicirratus, C. furcatus, Levinsenia flava, Paradoneis mikeli and Paraonides myriamae are recorded for the first time from the study region and two new species are described. Aricidea (Strelzovia) parabelgicae n. sp. is characterized by the absence of a frontal antenna, branchiae up to 7 pairs and beginning in chaetiger 5 and the ventral lip not indenting at chaetiger 2. Paradoneis andreae n. sp. is characterized by bearing single spine-like neurochaetae in posterior chaetigers and forked modified notochaetae, and by possessing 14–19 pairs of branchiae. A redescription of Paraonides nordica Strelzov, 1968 based on type material is also provided. A key to all the Paraonidae species known from the area, including also species not found in this investigation, is included.